Expanding perspectives on Air Pollution in Cities - Rasmus Reeh (Geoforum Perspektiv, 2021)
The science of air quality is gaining a lot of new grounds in recent years due to new  advances in sensors, data collection, and computing technologies. New sensors are  moved out the laboratories and on to the streets, where they are able in measuring at ultrafine and molecule scales. These data are propelled into health analyses documenting new correlation to a wide array of physical and neurological diseases.